2019
DOI: 10.1021/acs.jafc.9b06126
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Secondary Metabolites from Actinomycetes: Structure Diversity, Modes of Action, and Their Roles in the Development of Herbicides

Abstract: Weeds had caused significant loss for crop production in the process of agriculture. Herbicides have played an important role in securing crop production. However, the high reliance on herbicides has led to environmental issues as well as the evolution of herbicide resistance. Thus, there is an urgent need for new herbicides with safer toxicological profiles and novel modes of action. Actinomycetes produce very diverse bioactive compounds, of which some show potent biopesticidal activity. The herbicidal second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 165 publications
0
18
0
Order By: Relevance
“…Studies have already demonstrated actinomycetes metabolites active against bacteria (27), fungi (28), viruses (29), nematodes (30), and insects (31), as well as compounds with antitumor (32) and herbicide (33) activities. Some species can also produce enzymes of industrial interest, such as chitinases, cellulases, and amylases (34), and enzymes involved in plant growth promotion, like phosphatases and nitrogenases (35).…”
Section: Actinomycetes: a Rich Source Of Bioactive Compoundsmentioning
confidence: 99%
“…Studies have already demonstrated actinomycetes metabolites active against bacteria (27), fungi (28), viruses (29), nematodes (30), and insects (31), as well as compounds with antitumor (32) and herbicide (33) activities. Some species can also produce enzymes of industrial interest, such as chitinases, cellulases, and amylases (34), and enzymes involved in plant growth promotion, like phosphatases and nitrogenases (35).…”
Section: Actinomycetes: a Rich Source Of Bioactive Compoundsmentioning
confidence: 99%
“…rbES331 (Table 2) that also showed antifungal activity through diffusible compounds. Actinobacteria produce diverse secondary metabolites that inhibit different biological pathways in microorganisms and plants [64]. For example, the non-proteinogenic amino acid 4-Chlorothreonine, isolated from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need for expansion of crop production. However, weeds have always affected the growth and development of crops by the competition for light, space, nutrients, and water, leading to severe reductions in global crop yields . Synthetic herbicides have played a pivotal role in weed management by increasing both crop quality and yield and reducing labor costs .…”
Section: Introductionmentioning
confidence: 99%